One-stage release by double surgical approach for neglected congenital vertical talus: results in a series of walking children in Tanzania. Issue 6 (November 2019) - Sanzarello, Ilaria; Nanni, Matteo; Perna, Fabrizio; Traina, Francesco; Faldini, Cesare
Abstract : Congenital vertical talus is an uncommon rigid flatfoot deformity present at birth, producing pain and disability if untreated. This study reports results and complications in a series of walking children affected by neglected congenital vertical talus treated by one-stage release through a double surgical approach in a hospital sited in the Tanzanian rural outback. Between 2009 and 2014, nine consecutive congenital vertical talus were observed in five patients (three males and two females) aged between 2 and 4 years. In two children, the deformity was idiopathic, in two it was associated to distal arthrogryposis and in one to Larsen syndrome. The surgical procedure was performed through a posteromedial and a lateral incision and included extensive soft tissue release and reduction of talo-navicular and subtalar joint, pinned with percutaneous Kirschner wires. The talar axis-first metatarsal base angle (TAMBA) was measured preoperatively and at follow-up. Results were summarized using the Adelaar score and the PODCI (Pediatric Outcomes Data Collection Instrument) questionnaire. The mean follow-up was 2.6 years (2–4). No major intraoperative complications were observed. The TAMBA passed from 74.4° (range 68–82°) to 20.2° (range 18–24°). No talar osteonecrosis was observed. The results were excellent in three cases, good in five cases and fair in one (Adelaar score). The mean postoperative PODCI score was 48 (range 38–60). None of the patients underwent further surgery. In case of neglected congenital vertical talus and limited health resources, this surgical technique has proved to be a viable option, providing satisfactory results, with low rate of surgical and postsurgical complications.